Strategic planning for the textile and clothing supply chain - Hussain, Deedar (2012)
The expansion of textile and clothing production to Asian regions has both, increased competition and created a need for integration with the global supply chain. Strategies are being designed to improve competitiveness and responsiveness of the chains by increasing the diversification of products and value addition. This study formulates and examines the potential of such strategies and their implementation for textile and clothing chains originating from Pakistan. The strategies were developed based on a SWOT analysis followed by their prioritization through Saaty´s AHP and ANP. This work extends the previously developed phase of strategic planning to the implementation phase. Here we analyse the strategic plans using the Simple Additive Weighting (SAW) method and taking into account relevant factors such as cost, time and implementability.